The effects of food withdrawal and darkening on lipid peroxidation of laying hens in high ambient temperatures - Naziroglu, M; Şahin, Kazım; Simsek, H; Aydilek, N; Ertas, ON (M H Schaper Gmbh Co Kg, 2000)
The aim of this study was to investigate the effects of feed withdrawal and darkening on the antioxidative status of laying hens in high ambient temperatures between 30-40 degrees C. We determined Vitamins A and E, lipid peroxidation as thiobarbituric-acid reactive substances (TBARS), glutathione peroxidase (GSH-Px) and reduced glutathione (GSH) in the serum, liver and muscle. Sixteen week old hens (Ross Brown) were divided into 3 groups of 30 hens each. The first group was used as a control. Hens in the second (feed withdrawal) group were subjected to feed removal between 14-18 h during the summer. Hens in the third (darkening) group were subjected to darkening of the hens house with black curtains between 14-18 h. At the end of 16 weeks, blood serum, liver and breast muscle samples were taken from all animals and analysed. Vitamins A and E levels in serum and liver were significantly (P < 0.05, P < 0.01) higher in feed withdrawal and darkened groups than in control group whereas the serum levels of the darkening group were highest. GSH-Px activity and GSH level in liver and muscle were also significantly (P < 0.05, P < 0.01) higher in feed withdrawal and the darkening group than in control. However, TEARS levels in liver and muscle were significantly (P < 0.05, P < 0.01) lower in feed withdrawal and darkening groups compared with control group, whereas the level of the darkening group was the lowest. In conclusion, we observed that feed withdrawal and darkening of hens in high temperatures during summertime resulted in an increase of antioxidant enzymes and vitamins levels and in a decrease of lipid peroxidation.
Keywords: vitamin A; vitamin E; lipid peroxidation; feed withdrawal; darkening